Strategic Alliances or M&As? Qualitative Case Studies of Huawei and Geely in Emerging Chinese Market - Zhang, Jinghuan (2017)
Globalization has become the main topic for both practitioners and researchers these years. Due to the reforms of economics and structure in many developing countries, outward FDI in emerging markets boomed since the 1990s. China as one of the leading emerging markets with a sheer size of potential market and rapid economic growth, has become a major region of conducting outward FDI activities in recent years. Literately, the determinants of entry mode have already been analysed in the previous studies and the majority of these studies solely dedicated on one type of entry mode- strategic alliances or acquisitions. Thus, the purpose of the research is to explore the key motives of the entry mode strategies for both acquisition and alliances and choose a most appropriate method for emerging Chinese market. This dissertation exploited the qualitative research method and introduced the case studies of two famous Chinese brands- Huawei and Geely, by discussing their entry mode strategies in developed European and US markets. Finally, the differences and potential outcomes of choosing two strategies were identified in depth under three factors, namely, transaction costs factors, resource based factors and institutional based factors, which Chinese MNEs should carefully take into consideration before expanding abroad.